IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT BY APPLYING ANAGRAM PLUS FLASHCARDS AT THE SMP NEGERI 7 PEMATANGSIANTAR - Sartika - Manurung (Universitas Negeri Medan, 2014)
This study focused to improve Students’ Vocabulary Achievement by Applying Anagram Plus Flashcards. This study was conducted by using classroom action research. The subject of this study was students in class VII-7 of SMP Negeri 7 Pematangsiantar. There were 32 students taken as the subject. The instrument for collecting data were the test for vocabulary and diary notes, questionnaire sheets, observation sheet, and interview for process of teaching and learning vocabulary. The data were analyzed by descriptive analysis. The result of the research showed that the mean of students’ score in pre-test was 56.41, the mean of students’ score in post-test I was 69.22. The mean of students’ score in post-test II was 76.72. There were improvement of students’ achievement from 56.41-76.72 about 20.31 point and that score (76.72) was excelled the indicator (75). Based on diary notes, questionnaire sheets, observation sheet, and interview, it found that teaching and learning process ran well. Students were active, cooperative, enthusiastic and interested in learning vocabulary. There were 16 students (50%) agreed that the students active in learning process, 20 students (62.5%) were interested, 20 students (62.5%) were enthusiastic and 19 students (59.37%) were agreed that strategy of learning was effective. It can be concluded that the application of anagram plus flashcards had successfully improved the students’ vocabulary achievement at the SMP Negeri 7 Pematangsiantar. Keywords: Improve, Anagram Plus Flashcards, Vocabulary, Data, Achievement